Competencias profesionales para la gestión de emisoras universitarias en España - Ortiz Sobrino, Miguel Ángel; Marta-Lazo, Carmen; Contreras-Pulido, Paloma (Cuadernos INFO, 2021)
Este artículo presenta los resultados de una investigación sobre las competencias profesionales necesarias para la gestión en las emisoras universitarias españolas. Como técnica de investigación, se aplicó una encuesta online a sus directores, validada por seis académicos de diferentes universidades españolas vinculados a las áreas de conocimiento de Ciencias de la Comunicación y de Ciencias de la Educación, que se completó con una entrevista a dos directoras de emisoras universitarias. Los resultados revelan la importancia de las competencias para la planificación, la gestión y la organización del trabajo, así como una considerable relevancia de las habilidades sociales
Professional competences for the management of university radio stations in Spain
University radio stations are media that have a long history at the international level, mainly in Latin America and in some European countries. However, in Spain, their strong emergence begins in the 21st century thanks, among other things, to the possibilities offered by the Internet and the technological convergence. There are currently almost 30 stations that make up a diverse map of this type of media in the country. This has led to a research work corpus focused mainly on the content and shape of these stations programs and their possible social function, leaving a research niche concerning who constitute the teams that make them a reality. Thus, this article presents the results of a research into the professional skills required for management in Spanish university radio stations. As a research technique, we applied an online survey to their directors, validated by six academics from different Spanish universities linked to Communication Sciences and Education Sciences, which was completed with an interview with two female directors of university radio stations. The results reveal the importance of competencies for planning, management and organization of work, as well as a considerable relevance of social skills, and they could be taken into account to update the curricular content of university degree courses related to this medium.
Keywords: radio universitaria; competencias profesionales; perfiles profesionales; periodismo; comunicación audiovisual; university radio; professional skills; professional profiles; journalism; audiovisual communication; Emerging